Problem Analysis in the Development Needs of the Problem Based Learning and Discovery Learning Integrated Learning Model Tools Biology Concept Improvement of Students at SMA Negeri 1 Samarinda - Wiwik Wiwik; Vandalita M Rambitan; Lambang subagiyo (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2018)
There are two purposes of this study: 1) To generate student understanding of scientific learning approach to improve student comprehension on Biology concept at SMAN 1 Samarinda. 2) To generate integrated learning tools development between Problem Based Learning and Discovery Learning to improve comprehension on Biology concept at SMAN 1 Samarinda. In accordance with teacher needs, observation results analysed using descriptive qualitative methods, three main findings were obtained: 1) teachers were still likely to encounter difficulties when applying teaching and learning process in class, 2) The main difficulties experienced by teachers were due to time constraints in developing learning tools, 3) The learning tools development of the Problem Based Learning and Discovery Learning integrated learning model were considered to be important to improve student comprehension on Biology concept. The learning model used was the Problem Based Learning and Discovery Learning Integrated Learning Model .